(untitled) (International Journal of Pharmacy and Life Sciences, 2014)
Physico-chemical study of water is important to ascertain the effectiveness of the treatment system and make the necessary recommendations for further study and improvement of the water management system. Physico-chemical analysis of temperature, pH, Total Hardness, Total alkalinity, Biological Oxygen Demand, Dissolved Oxygen, Phosphates, Nitrates, and Sulphates of dam water, tap and water treatment effluent was carried out from fourteen sampling locations in September and November 2013 in order to assess the water quality index of water used by University of Eastern Africa, Baraton and her environs. From the study the level of phosphates and sulphates were found to be high in comparison with the provided WHO standards and therefore proper care should be taken to avoid the accumulation of these compounds in the water source.